MEMPERKUAT PERAN PUSTAKAWAN DALAM MEWUJUDKAN LAYANAN PERPUSTAKAAN PERGURUAN TINGGI YANG PRIMA DAN UNGGUL - Bambang Hermanto (Central Library of Universitas Sebelas Maret, 2016)
The establishment of the college library aims to support the achievement of the vision of the mission of higher education in implementing the Tri Dharma College, namely education, research, and community service. The role of the library in this regard include satisfying the information needs of academicians, providing library materials, provide study rooms, providing lending services and providing information services. Library is the heart of the college. Library as a source of information must be managed properly and professionally. To realize the excellent service and superior, then the college library services should beroreintasi on satisfaction and customer focus. For strengthening the role of the librarian, then the librarian skills and knowledge on the basics of the service must be improved through education, training, workshops, workshops and seminars, in order to achieve service excellence and superior library.There is also the strategy of librarians in strengthening its role in the realizationof library services college superior and primed to consider several things, amongothers: (1) improving the competence of librarianship, (2) maintain the appearance, (3) confident, smiling, being friendly, and friends, (4) listen to each conversation and received no complaints with either, (5) speak the language properly and clearly, (6) enthusiastic in providing services and show the ability, (7) if it can not resolve the existing problems, can work together with other librarians.